Continuity of care during severe civil unrest with a model of community-based HIV care: a retrospective cohort study from HaitiResearch in context - Patrice Joseph; Rochelle Sun; Colette Guiteau; Marc Antoine Jean Juste; Nancy Dorvil; Stalz Vilbrun; Rode Secours; Karine Severe; Parnel Raymond; Fernande Cetoute; Wilnide Jean Baptiste; Guyrlaine Forestal; et al. (Elsevier, 2024)
Summary: Background: There are limited data on the effectiveness of differentiated service delivery (DSD) for HIV care during sociopolitical turmoil. We assessed outcomes with a DSD model of care that includes patient choice between community-based antiretroviral therapy (ART) centres, home-based ART dispensing, or facility-based care at GHESKIO clinic during a period of severe civil unrest in Port-au-Prince, Haiti. Methods: This retrospective analysis included data on patients with at least one HIV visit at GHESKIO between May 1, 2019, and December 31, 2021. Multivariable logistic regression models were used to assess predictors of attending ≥1 community visit during the study period, and failure to attend timely visits. HIV-1 RNA test results were reported among patients who had been ART for ≥3 months at last visit. Findings: Of the 18,625 patients included in the analysis, 9659 (51.9%) attended at least one community visit. The proportion of community visits ranged from 0.3% (2019) to 44.1% (2021). Predictors of ≥1 community visit included male sex (aOR: 1.13; 95% CI: 1.06, 1.20), secondary education (aOR: 1.07; 95% CI: 1.01, 1.14), income > $USD 1.00/day (aOR: 1.24; 95% CI: 1.14, 1.35), longer duration on ART (aOR: 1.08 per additional year; 95% CI: 1.07, 1.09), and residence in Carrefour/Gressier (p < 0.0001 in comparisons with all other zones). Younger age and shorter time on ART were associated with late visits and loss to follow-up. Among 12,586 patients with an on-time final visit who had been on ART for ≥3 months, 11,131 (88.4%) received a viral load test and 9639 (86.6%) had HIV-1 RNA < 1000 copies/mL. Interpretation: The socio-political situation in Haiti has presented extraordinary challenges to the health care system, but retention and viral suppression rates remain high with a model of community-based HIV care. Additional interventions are needed to improve outcomes for younger patients, and those with shorter time on ART. Funding: No funding.